Materials science and technology :a comprehensive treatment /. Volume 3B., Electronic and magnetic properties of metals and ceramics Part 1 / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol editor : K. H. Jurgen Buschow - Buschow, K. H. Jurgen
Vol 3B. Electronic and magnetic properties of metals and ceramics Part II in 1994